LIVING & LEARNING ENGLISH-CHALLENGES BEFORE THE UNDERGRADUATE ENGINEERING STUDENTS IN INDIA - Sawhney, Ekta (PEOPLE: International Journal of Social Sciences, 2016)
Learning to speak & write in the English Language is a big challenge for learners in India who hail from different non-English speaking backgrounds. Assimilating English is one of the toughest jobs on the part of the Learners & is more difficult on the part of the teachers of English. An undergraduate Communicative English class is worst affected because of the unwillingness of the learners to speak & converse in the Language. This may be because of their backgrounds or their previous conditioning. The current paper proposes ways & means to tackle this difficulty & to enable the speakers to shed their inhibitions, & converse freely in the Language.